ANALISIS PROSES MANUFAKTUR MESIN PEMOTONG KERUPUK IKAN DENGAN METODE DESIGN FOR MANUFACTURE AND ASSEMBLY (DFMA) - Ilham Ibrahim (2021)
Indonesia known as a maritime country where most of it consists broad water area with the result of its marine wealth -fish, are processed into snacks. Fish-based snack favored by the people of Indonesia is fish crackers. A device that can help micro, small and medium enterprises (MSMEs) produce fish crackers is a fish crackers slicer machine. However, fish crackers slicer machines that are sold in mass selling market are quite expensive and less efficient, this can be avoided by using the Design for Manufacture and Assembly (DFMA) method. By using the DFMA method, it can reduce the production cost of the fish crackers slicer machine without reducing the function of the device and increase the MSMEs producer's production efficiency. According to the DFMA method, it can be produced a final machine product with the design efficiency in the amount of 11.25% and has a production capacity in the amount of 120Kg/Hours by only costs Rp 1.637.680,69.